Direct numerical simulation study on relationship between Ranque-Hilsch effect and turbulence in high-speed swirling flow inside a cylindrical vortex chamber - Taihei YAMAMOTO; Yuji HATTORI (Nihon Kikai Gakkai ronbunshu)
The Ranque-Hilsch vortex tube (RHVT) is a device which can separate compressed gas into high and low energy flows only through its own fluid motion by generating a high-speed swirling flow inside a cylindrical vortex chamber. The energy separation phenomenon of RHVT is called the Ranque-Hilsch effect (RH effect). Although numerous studies have been conducted over the past 90 years since the discovery of the RH effect (1933), the energy separation mechanism has not been elucidated. Previous studies have suggested that the RH effect is caused by the unsteadiness of a high-speed swirling flow inside the cylinder, such as turbulence and acoustic phenomena. However, the unsteady characteristics have not been clarified because it is difficult to obtain time evolution data sufficiently guaranteed physical reliability. In this paper, high-speed unsteady swirling flow inside the cylindrical vortex chamber of RHVT is calculated by direct numerical simulation for the first time. Because the Reynolds number of the flow inside RHVT is high, it is difficult to use direct numerical simulation due to the high computational costs. To reduce the computational costs, we performed direct numerical simulation by setting the viscosity of the working fluid higher than the air. The viscous coefficient of the working fluid is set equal to or larger than 100 times that of the air. We find out that the turbulence intensity is axisymmetric, and the closer to the axial position of inlet, the stronger turbulence occurs. By comparing flows with different viscosities of the working fluid, we also find out that there is a relationship between the RH effect and turbulence in a high-speed swirling flow inside the cylinder, as the energy separation effect increases with increasing turbulence intensity.